Refining the Depression-Nicotine Dependence Link: Patterns of Depressive Symptoms in Psychiatric Outpatients with Current, Past, and No History of Nicotine Dependence - Leventhal, Adam M. (2008)
The aim of this study was to elucidate the depression-nicotine dependence link by evaluating which specific depressive symptoms are uniquely associated with nicotine dependence in psychiatric outpatients. Participants were assessed using structured clinical interviews which yielded psychiatric diagnoses and clinical ratings on a wide variety of depressive symptoms. Depressive symptoms were compared across three groups: (1) patients with no history of nicotine dependence (NND; n=1015); (2) patients with past nicotine dependence in full remission for at least 2 months (PND; n=211); and (3) patients with current nicotine dependence (CND; n=342). Participants with CND evidenced elevations on certain typical-vegetative, melancholic, and dysphoric depressive symptoms as compared to patients with NND and (to a lesser extent) patients with PND. Group differences were most consistent for depressed mood, anhedonia, appetite/weight loss, psychomotor disturbance, fatigue, and insomnia. Differences were least apparent for atypical symptoms. The symptomatic profiles of PND and NND patients were virtually indistinguishable. Certain vegetative, melancholic and dysphoric depressive symptoms are closely associated with nicotine dependence and could play an important etiological role in depression-nicotine dependence comorbidity.